PERCEPTION OF TOURISTS ON ENVIRONMENTAL IMPACT OF TOURISM IN SHIMLA - Pooja Chauhan, Dr. Kushal Singh, Dr. Arun Singh Thakur, (Chelonian Research Foundation, 2023)
Shimla is mostly recognized for its stunning natural surroundings. This paper is on how tourists perceive the Shimla environment. The study demonstrates how tourism affects the area. Tourism has both beneficial and bad effects on the ecosystem, according to the paper. Positive effects on tourism promotion and natural area conservation; negative effects on the natural environment, such as pollution, traffic congestion, water depilation, and overcrowding. The paper also presents the tourist department's initiative to encourage tourism while protecting the area's ecosystem. The paper is based on both primary and secondary data. The online questionnaire was created, and the respondents are tourists who have visited the area. Keywords: Shimla environment,tourism effects,overcrowding, tourist perception, pollution, natural environment.